INTEGRITAS LAPORAN KEUANGAN: TINJAUAN TERHADAP PERAN UKURAN KAP, KOMISARIS INDEPENDEN, DAN STRUKTUR TATA KELOLA PERUSAHAAN: Ukuran KAP, Komisaris Independen, Struktur Tata Kelola Perusahaan dan Integritas Laporan Keuangan - Mukoffi, Ahmad; As’adi, As’adi; Dina Ekasari, Luh; Himawan Wibisono, Sukarno; Sarlin, Lusia (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
This study aims to determine the effect of the variable size of the cap, independent commissioner and corporate governance structure on the integrity of financial statements. The corporate governance structure in this study is measured by institutional ownership, managerial ownership and audit committees. This research is quantitative descriptive. The population in this study are textile and garment companies listed on the Indonesian Stock Exchange for the 2020-2022 period. Purposive Sampling was used in determining the sample in order to obtain a sample of 18 companies that met the criteria. This study uses multiple linear regression analysis. The results showed that the size of the cap, independent commissioners and institutional ownership had a significant effect on the integrity of financial statements, while the audit committee had a negative and significant effect on the integrity of financial statements. Managerial ownership has no significant effect on the integrity of financial statements.